Mengurai Kontroversi Kafir: Konteks Historis dan Linguistik QS. At-Taubah [9]: 5 - Taftazani, Tubagus Syafiq (Sunan Kalijaga Islamic State University, 2022)
The debate over changing the term kafir to non-Muslim has become a prominent issue in Indonesia in recent years. This study aims to uncover the contextual meaning behind the interpretation of QS. At-Taubah: 5, which is central to this debate. Utilizing a contextual approach, the research focuses on both linguistic and historical analyses of QS. At-Taubah: 5. Linguistically, this verse is often quoted out of context by hardline Muslim groups without considering its connection to the surrounding verses, as well as related verses such as QS. al-Anfal 54-58. Historically, the verse is closely linked to the context of war arising from treaty violations. In pre-Islamic Arab society, war was a deeply ingrained part of the culture, and this verse specifically addresses conflicts triggered by treaty violations by certain groups, rather than targeting all polytheists. The findings suggest that the relevance of QS. At-Taubah: 5 needs to be reconsidered in the modern context, especially given that wars are now infrequent, particularly in Indonesia. Furthermore, the categorization of infidels is likely to evolve over time in response to changing societal norms and political dynamics. A reinterpretation using a contextual approach can provide a clearer understanding of the verse and help prevent its misuse to justify acts of violence.